1973
DOI: 10.1177/140349487300100102
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae of Accidental Near-drowning in Childhood

Abstract: Patients admitted to hospital because of near-drownings were followed-up 2–7 years after the admissions. The material comprises 36 children and 15 adults, which is the total number of patients cared for because of accidental near-drownings within the Uppsala Hospital Region 1964–1968. The region contains one-sixth of Sweden's population. Hospital records were examined and parents of the children were interviewed by telephone. Two seriously disabled cases were found. The annual figure for severely and permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The development of posthypoxic encephalopathy is the most common cause of death in hospitalized victims who have suffered from the drowning process. 19,20 No two cases of drowning are identical. The type, temperature, and quantity of water aspirated may differ, and the victim's state of health before drowning may be important.…”
Section: The Drowning Processmentioning
confidence: 99%
“…The development of posthypoxic encephalopathy is the most common cause of death in hospitalized victims who have suffered from the drowning process. 19,20 No two cases of drowning are identical. The type, temperature, and quantity of water aspirated may differ, and the victim's state of health before drowning may be important.…”
Section: The Drowning Processmentioning
confidence: 99%
“…The development of posthypoxic encephalopathy with or without cerebral edema is the most common cause of death in hospitalized drowning victims. 38,39 Most resuscitations begin at the scene of the drowning and not at a hospital, making on-scene data extremely important. Furthermore, many, or possibly most, drowning victims have mild symptoms, recover at the scene, and may or may not be transported to a hospital.…”
Section: Definitionsmentioning
confidence: 99%
“…Every year a number of near-drowning victims are treated in children's hospitals. The prognosis for a complete recovery is held to be very good (4,13). In the material of 36 near-drowned children Eriksson et al found two seriously disabled cases.…”
mentioning
confidence: 99%